Place and type of delivery along with assistance during delivery among women residing in a village in South Delhi: Low performance pocket within a high performing state - Pardeshi, Geeta; Roy, Neelam; Verma, Anita; Ranjan, Sneha; Kishore, Jugal (Indian Journal of Community Health, 2017)
Background: Various initiatives have been taken under the National Health Mission to improve coverage of institutional deliveries. Yet there are disparities in the proportion of institutional deliveries between states. A high proportion of non-institutional deliveries was noted in a village under PHC Fatehpur Beri in South Delhi. Aims and Objectives: To study the place, assistance and type of deliveries in this village during the years 2007 to 2016 which is the period when several initiatives were taken up to promote institutional deliveries. Material & Methods: A community based cross-sectional study was conducted in Kharak village under PHC, Fatehpur Beri in which data on place and year of delivery, assistance during delivery, type and outcome of deliveries in the period 2007 to 2016 were collected. In analysis, the data for two five year periods were compared using Fishers exact test and odds ratio was calculated with 95% confidence intervals. Trends were assessed by using Mantel-Haenszel test. Changes in the delivery characteristics of two consecutive deliveries were assessed. Results: Of the 312 deliveries, 106 (34%) were institutional deliveries out of which 98 (92%) were in public hospitals. A total of 113 (36%) were assisted by doctors and nurses 44 (14%) were caesarean section deliveries. The proportion of institutional deliveries had increased significantly from 23% in the years 2007-2012 to 42 % in the period 2012 to 2016. [X2=11.76, df=1, p=0.001, OR=2.37(1.44-3.91)]. The proportion of women assisted by trained health professionals during the deliveries also showed a significant rise from 26% to 44% between these time periods. [X2=11.39, df =1, p=0.001, OR=2.3(1.41-3.75)] There was no significant difference in the proportion of caesarean section deliveries between the two study periods. [X2=0.167, df=1, p=0.683, OR=0.87(0.46-1.66)]. There was a significant increase in the proportion of institutional deliveries over the ten year period from 23% to 56% [X2=17.84, df=1, p=0.00]. Conclusion: There are pockets of poor performance on institutional deliveries within high performing states. There is increasing trend in institutional deliveries and assistance by trained health professional in the village but there is huge scope to improve the coverage to match the state and national figures. There is a need to identify the challenges and customize interventions to address them in such pockets